Pengaruh Ukuran Perusahaan, Karakteristik Perusahaan, Kepemilikan Asing dan Komisaris Independen Terhadap Sustainability Reporting Pada Perusahaan Manufaktur yang Terdaftar di BEI - I Gede Cahyadi Putra; Made Edy Septian Santosa; Ni Kadek Dwi Putri Juliantari (WACANA EKONOMI (Jurnal Ekonomi, Bisnis dan Akuntansi), 2023)
Sustainability reporting is a reporting that is disclosed voluntarily by the company and is related to three aspects, namely economic, social, and environmental. The sustainability report is prepared according to the GRI (Global Reporting Initiative) guidelines. This sustainability report can be an attempt by the company to describe the level of concern for the community. This study aims to analyze the effect of firm size, leverage, profitability, foreign ownership and independent commissioners on sustainability reporting in manufacturing companies listed on the IDX.The sample of this research is 14 manufacturing companies listed on the Indonesia Stock Exchange for the period 2018-2020. Determination of the sample using purposive sampling method. The analytical tool used is multiple linear regression. The results show that the variables of firm size, profitability and independent commissioners have a positive effect on sustainability reporting. Meanwhile, leverage has a negative effect on sustainability reporting and foreign ownership has no effect on sustainability reporting. The results of this study found that the size of the disclosure of sustainability reporting is only influenced by company size, leverage, profitability and independent commissioners, while foreign ownership in this study cannot affect the disclosure of sustainability reporting.